Experimental quantification of Geant4 PhysicsList recommendations: methods and results. Issue 7 (December 2015) - Basaglia, Tullio; Han, Min Cheol; Hoff, Gabriela; Kim, Chan Hyeong; Kim, Sung Hun; Pia, Maria Grazia; Saracco, Paolo
Abstract: The Geant4 physicsjists package encompasses predefined selections of physics processes and models to be used in simulation applications. Limited documentation is available in the literature about Geant4 pre-packaged PhysicsLists and their validation. The reports in the literature mainly concern specific use cases. This paper documents the epistemological grounds for the validation of Geant4 pre-packaged PhysicsLists (and their accessory classes, Builders and PhysicsConstructors) and some examples of the author's scientific activity on this subject.